Evalution of normal CSF velocities at the level of aqueduct amongst Indian rural adults using 1.5 Tesla MRI - Dr Sankalp Dilip Shirsath; Dr Raunaklaxmi A. Shirsath- Talele; Dr Apurva S. Kale-Shirsath; Dr Pooja Shah (International Journal of Clinical and Biomedical Research, 2021)
Rapid advances in imaging techniques have remarkably improved the diagnosis and treatment of central nervous system (CNS) disorders, with magnetic resonance imaging (MRI) being the most recent. New MRI applications are continually being developed, providing improved assessment of CNS disorders and their response to treatment, such as cerebrospinal fluid (CSF) movement, the alteration of which results in many clinical disorders with hydrocephalus (including normal pressure hydrocephalus), cystic CSF collections, and Chiari malformations being more common. CSF flow MRI can be used to discriminate between several disorders and provide information in the pre and postoperative evaluation of clinical disorders and surgical intervention. The aim of the study is to calculate and evaluate CSF flow velocities at the level of the aqueduct. MRI brain with CSF flow study was done in 40 patients. These patients were in the age group of 20-60 years and came with no significant clinical complaints. Phase contrast MRI scanning was used following the CSF quantitative flow protocol. A transverse single slice quantitative flow measurement was used to calculate the mean CSF flow velocity. Calculation of the CSF flow at the level of the cerebral aqueduct provides the best quantification of the CSF volume. It concluded that the normal range of the values of the CSF in normal individuals comes out to be 0.05 ±0.12 cm/sec.